2020
DOI: 10.1038/s41598-020-75767-2
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning prediction for mortality of patients diagnosed with COVID-19: a nationwide Korean cohort study

Abstract: The rapid spread of COVID-19 has resulted in the shortage of medical resources, which necessitates accurate prognosis prediction to triage patients effectively. This study used the nationwide cohort of South Korea to develop a machine learning model to predict prognosis based on sociodemographic and medical information. Of 10,237 COVID-19 patients, 228 (2.2%) died, 7772 (75.9%) recovered, and 2237 (21.9%) were still in isolation or being treated at the last follow-up (April 16, 2020). The Cox proportional haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 34 publications
7
131
0
1
Order By: Relevance
“… Death 9 32/734 (4.4) 98/2,817 (3.5) 10/159 (6.3) 12/273 (4.4) 1.15(0.73–1.82) - Severity (10) 9 ( Hirashima et al, 2021 ) Japan Retrospective cohort 47.51 61 2/61 (3.3) - 0/2 16/59 (27.1) - - - 0.53 (0.02-11.57) - Severity (11) 7 ( Yang et al, 2020 ) UK Prospective cohort 67.8±8.12 1,951 442/1,951 (22.7) Depression= 231/442 (52.3) Anxiety= 165/442 (37.3) Stress Related Disorder=10/442 (2.3) Substance Misuse=212/442 (50.0) Psychotic Disorders=19/442 (4.3) 120/442 (27.1) 256/1,509 (17.0) - 68/231 (29.4) 2.03 (1.59−2.59) - Year, sex, race or ethnicity, Townsend deprivation index, educational attainment, annual household income, body-mass index, smoking status, and co-morbidities(12). Death 9 ( Lee et al, 2020a ) South Korea Retrospective cohort - 781 236/781 (30.21%) Depressive Disorder=228/497 (45.9) Anxiety=205/497 (41.2) Bipolar Disorder= 72/497 (14.5) Psychotic Disorder=62/497 (12.5) Schizophrenia=41/497 (8.2) Substance Use Dis Related Diseases=18/497 (3.6) 30/236 (12.7) 37/545 (6.8) - - - 2.00 (1.20-3.32) Age, sex, and index month Death 7 ( An ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Death 9 32/734 (4.4) 98/2,817 (3.5) 10/159 (6.3) 12/273 (4.4) 1.15(0.73–1.82) - Severity (10) 9 ( Hirashima et al, 2021 ) Japan Retrospective cohort 47.51 61 2/61 (3.3) - 0/2 16/59 (27.1) - - - 0.53 (0.02-11.57) - Severity (11) 7 ( Yang et al, 2020 ) UK Prospective cohort 67.8±8.12 1,951 442/1,951 (22.7) Depression= 231/442 (52.3) Anxiety= 165/442 (37.3) Stress Related Disorder=10/442 (2.3) Substance Misuse=212/442 (50.0) Psychotic Disorders=19/442 (4.3) 120/442 (27.1) 256/1,509 (17.0) - 68/231 (29.4) 2.03 (1.59−2.59) - Year, sex, race or ethnicity, Townsend deprivation index, educational attainment, annual household income, body-mass index, smoking status, and co-morbidities(12). Death 9 ( Lee et al, 2020a ) South Korea Retrospective cohort - 781 236/781 (30.21%) Depressive Disorder=228/497 (45.9) Anxiety=205/497 (41.2) Bipolar Disorder= 72/497 (14.5) Psychotic Disorder=62/497 (12.5) Schizophrenia=41/497 (8.2) Substance Use Dis Related Diseases=18/497 (3.6) 30/236 (12.7) 37/545 (6.8) - - - 2.00 (1.20-3.32) Age, sex, and index month Death 7 ( An ...…”
Section: Resultsmentioning
confidence: 99%
“…This analysis provides evidence suggesting that the need of mechanical ventilation, ICU admission and mortality is higher among COVID-19 patients who were diagnosed with mental disorder by the provided odds ratio by 63.8% (OR= 1.76, 95% CI=1.29-2.41). ( An et al, 2020 ; Batty et al, 2021 ; Cavallaro et al, 2020 ; Collaborative, 2021 ; Cummins et al, 2021 ; Fond et al, 2020 ; Giannoglou et al, 2020 ; Hirashima et al, 2021 ; Jeon et al, 2020 ; Lee et al, 2020a ; Lee et al, 2020b ; McKeigue et al, 2020 ; Nemani et al, January 2021 in JAMA psychiatry; Wang et al, 2020 ; Yang et al, 2020 ; Yanover et al, 2020 ) This was also suggested in the fully adjusted as patients with mental disorders had 60.3% higher risk (OR=1.52, 95% CI= 1.20-1.93). ( Cavallaro et al, 2020 ; Fond et al, 2020 ; Jeon et al, 2020 ; Lee et al, 2020b ; Yang et al, 2020 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we analyse prognostic and factors associated with disease progression in 3944 SARS-CoV-2 positive patients by constructing an interpretable ML framework. In contrast to previous studies 1 , 2 , these included diagnosed patients outside hospitals, and thus included the entire spectrum of SARS-CoV-2 positive patients in the 2.6 million regional population.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis claimed by the healthcare providers and the actual diagnosis may differ because the dataset was established for recording claims and reimbursements. Thus, operational definition was used for determining the presence of medical conditions, as previously reported [ 21 ]. For example, hypertension was diagnosed when a patient on antihypertensive medication was admitted for the first time or visited outpatient clinic for a second time with the International Classification of Diseases 10 th revision (ICD-10) codes for hypertensive disease.…”
Section: Methodsmentioning
confidence: 99%